The Influence of Organizational Commitment, Professional Skepticism, and Internal Audit on Fraud Prevention in Inventory Management (A Case Study at PT Muda Cahaya Utama in Tangerang City) - Rusli; Dea Annisa (LPPM Sekolah Tinggi Ilmu Ekonomi 45 Mataram, 2026)
This study aims to examine and obtain empirical evidence on the influence of Organizational Commitment, Professional Skepticism, and Internal Audit on all employees of PT Muda Cahaya Utama. The research method used is quantitative with primary data collected through questionnaires distributed via Google Forms and measured using a 5‑point Likert scale. The sampling technique is convenience sampling, and the data are analyzed using multiple linear regression with SPSS version 29. The study uses a sample of 194 respondents. The results show that organizational commitment has a significant positive effect on inventory fraud detection, professional skepticism has a significant positive effect on inventory fraud detection, and internal audit has a significant positive effect on inventory fraud detection.